ПОКАЗАТЕЛИ КОЖНО-ГАЛЬВАНИЧЕСКОЙ РЕАКЦИИ У ЛЮДЕЙ С РАЗЛИЧНЫМ ТИПОМ ТЕЛОСЛОЖЕНИЯ (Eurasian Journal of Ecology, 2016)
This paper analyzes the relationship between the feature build, stamina, and an indicator of galvanic skin response, which characterizes the level of the hypothalamic-sympathetic-adrenal activity.